Penerapan scaffolding untuk pencapaian kemandirian belajar siswa - Elis Nurhayati (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2017)
The purpose of this study was to analyse the achievement of student learning independence through scaffolding application. This study was a quasi-experimental research with involving two classes using purposive sampling. The population in this study was the student of class VIII in one of the public junior high school in Tasikmalaya district involving two classes as the sample. The data collection technique used was non-test. The test instrument according to the indicator the ability while the non-test by questionnaire. The data analyse performance Method of Successive Interval. The research result showed that ability of the student who gets scaffolding learning is higher than the student who gets direct learning, the student learning independence of student who gets scaffolding learning is better than students who get direct learning, and the student learning independence of student who gets scaffolding is in the high category.